A SURVEY STUDY TO ASSESS THE DIETARY PATTERN AMONG ADOLESCENTS. - Agnihotri, Mrs. Laxmi; Hiremath, Sukanya; Kalakeri, Suneel; Jibate, Sunil; Supritha. M.; Yaranal, Varun; Muchandi, Veena (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Food pattern is very essential for proper growth and development of adolescents, during this period adaptation of healthy dietary patterns reflects on their physical, psychological balance of the adolescents. A study assessed to determine the food pattern among 150 adolescents aged between 13 to 20 years. A study setting is selected High school at vijayapur district. A quantitative survey study was conducted by using self administered questionnaires among 150 adolescents. Nearly 56 % of boys and 44% girls participate in the study. Majority 74% of adolescents belongs to the nuclear family and 36% belong to joint family. Regarding dietary pattern many of 25% adolescents are skipping morning breakfast.46% of adolescents favorite food is chats instead of using fruits and vegetables, 41% and 35% adolescents are enjoying in eating chats and pizza. 44% of adolescents are eating outside food more than 3 times per week.53% of adolescents are drinking cold drinks and only 35% are drinking fruit juice and others are using tea, coffee. The study concludes that many of the adolescents are not practicing the healthy dietary pattern so there is essential to implement awareness programmes on dietary pattern.